Análise da divulgação de capitais não financeiros do relato integrado - Diniz, Maria Luiza Farias (2020)
In the last few decades, companies have started to react differently when it comes to reporting their information to interested parties, starting to demand more than just financial information, because users' interest in information of an environmental and social nature has increased. To encourage companies to reveal non-financial information, the Integrated Report (IR) was created in 2010 aiming to develop a different way of acting, regarding to corporate disclosure. The IR interconnects the information of the corporate reports, making it the main tool for disseminating corporate information (financial and non-financial), presenting relevant information about the activities of the organizations. This new report model is composed of 6 (six) capitals: financial; manufactured; natural; human; social and relationship; and intellectual. In order to carry out this research, the disclosure of IR non-financial capital from companies belonging to 9 (nine) different economic sectors was calculated and analyzed, considering the period from 2014 to 2018. The companies participating in the research were identified according to the “Examples Database” of the Integrated Reporting <IR> itself. This research regarding the objectives is classified as exploratory and descriptive. Regarding the procedures, this research is bibliographic and documentary, with a qualitative and quantitative approach. For its development, the content analysis technique was used, which innovates research in this area, because it was carried out through mining data through the “R” software. For its execution, information related to the non-financial capital of IR was identified, calculated and analyzed, according to a checklist of keywords / related ones that are described before the information in the launching framework (Key Performance Indicators - KPIs), totaling 34 (thirty-four) indicators. Thus, it has as a general result considering the disclosure of the analyzed capitals that most organizations seek to insert in their reports information that refers to the indicators of the non-financial capital analyzed. In the analysis of the disclosure index (DI), some economic sectors had their results as maximum, which refers to (100%) in various indicators of nonfinancial capital of IR, thus standing out in relation to the voluntary disclosure available in the organizational reports. Finally, with regard to the comparisons of the economic sectors with the indicators of each non-financial capital analyzed, there are the sectors with the greatest highlights in relation to the highest averages achieved: energy, public utility and health. So that the organizations that compose them, make available, in a greater quantity than the others, information in their reports that refer to the key performance indicators according to the related words analyzed in this research.